Biofilm formation by Staphylococcus spp. isolated from local food markets at Baghdad city (World Journal of Experimental Biosciences, 2016)
Formation and presence of biofilm leads to rise concerning of human towards food industries, because Biofilm formation impact human health and his economic negatively Staphylococcus spp. is a pathogenic bacteria, can form biofilm when conditions are adequate, also its able to transition from human to the food and food-contact surfaces due to the nature and habit of these type of bacteria. Staphylococcus spp. was Isolated from different food samples in processing plant of food preparation, and identified based on 16SrRNA using T stag primer, also we used forward primer Sa442-1 and reveres primer Sa442-2 to confirm the identification of Staphylococcus aureus, from 36 isolates, 18 isolates was identified as S. aureus. The ability of bacteria to form biofilm was verified by the use of polystyrene microtiter plate assay with crystal violet staining. There were clear differences among Staphylococcus spp. isolates in biofilm formation, the ability was measured by determination of adhesion to polystyrene microtiter plates and compared with Bacillus spp. as a control positive and control negative. Isolates of Staphylococcus spp. showed different ability to form biofilm and adhere on polystyrene plates.